The Implementation of Religious Character Through Memorize Short Verses Of al-Quran and Daily Prayers in Elementary School - Yunischa, Eria (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2018)
The formation of religious character is indispensable for children in elementary education to face the negative effects of global challenges.This religious character education is obtained by the children of the Religious Education in the school. Islamic Religious Education has a very important role to shape the childs religious character. The full curriculum of Islamic Education requires teachers to be able to provide additional extracurricular activities. The most effective extracurricular program of Islamic Religious Education to shape the childs religious character is readingand writingQuran (In Indonesia : Baca Tulis Al-Qurâan / BTQ) by memorizingAl-Quran versesand daily prayers. This paper discusses the implementation of religious character education through memorized of short verses of Quran and daily prayers in elementary school as an effort of teacher in implementing the character education goals proclaimed by the Government of the Unitary State of the Republic of Indonesia.